(untitled) (Terr@ Plural, 2022)
This paper estimates the relevance of caves developed in different lithological contexts (carbonate, siliciclastic, ferriferous, and granitic) as defined on Decree 6.640/2008 and Normative Instruction # 2/2017 of the Brazilian Ministry of Environment, which consider only geological features. The method was applied in eight caves, two for each lithotype. It was analyzed whether the criteria adopted for the evaluation of caves’ relevance degree are efficient when just the geological features are considered. Analyzing just the geoforms the eight studied cavities were classified as of low relevance, as none reached the minimally significant parameter. However, based on geodiversity inventory we could ascertain that these caves do have important geological elements and could not be classified as of low relevance when analyzing these attributes in isolation. Therefore, there are inconsistencies in IN MMA # 2/2017 for the evaluation of aspects of cave geodiversity, so it is necessary to review the attributes and parameters of this normative aiming at more precise methods, especially those related to the aspects of underground geodiversity.